A systematic method for the analysis of energy supply reliability in complex Integrated Energy Systems considering uncertainties of renewable energies, demands and operations. (10th September 2020) - Su, Huai; Zio, Enrico; Zhang, Jinjun; Li, Zhenlin; Wang, Haifeng; Zhang, Fang; Chi, Lixun; Fan, Lin; Wang, Wei
Abstract: Integrated Energy Systems (IES) become more and more important for the sustainability in energy system development and for promoting the application of clean energy technologies. System complexity and various uncertainties interaction make it difficult to maintain a reliable energy supply. In this paper, a systematic method is proposed for energy supply reliability analysis in complex Integrated Energy Systems (IES). The developed method integrates stochastic modeling, supply capacity analysis and reliability evaluation, which is able to give more comprehensive knowledge of the ability of the IES for satisfying the energy needs under different, coupled uncertainties. Firstly, stochastic models are developed for each unit in IES, including renewable energy, customer demands and components in natural gas pipeline networks and electric power grids, according to their characteristics. Then, a two-stage optimization model is developed for simulating the operation strategies of IESs, and calculating the supply capacities under randomly generated scenarios. Finally, the reliability of supply is evaluated based on the results of the random simulations. The developed method is used to analyze the supply reliability of an assumed IES, to test its effectiveness. The results show the ability to provide valuable information from multiple perspectives including system, individual customer and resource allocation, for design, extension and management of IES. Highlights: A systematic method is developed for reliability of energy supply in IES. Different uncertainties can be coupled and analyzed in the proposed method. The complexities of system structure and dynamics are modeled in this framework. Supply reliability is analyzed from the aspects of system, customers and resources.